Significant decrease of saturation index in erythrocytes membrane from subjects with non-alcoholic fatty liver disease (NAFLD) - Notarnicola, Maria; Caruso, Maria Gabriella; Tutino, Valeria; Bonfiglio, Caterina; Cozzolongo, Raffaele; Giannuzzi, Vito; De Nunzio, Valentina; De Leonardis, Giampiero; Abbrescia, Daniela I.; Franco, Isabella; Intini, Vincenza; Mirizzi, Antonella; et al. (Lipids in health and disease, 2017)
The lipidomic profiling of erythrocyte membranes is expected to provide a peculiar scenario at molecular level of metabolic and nutritional pathways which may influence the lipid balance and the adaptation and homeostasis of the organism. Considering that lipid accumulation in the cell is important in promoting tissue inflammation, the purpose of this study is to analyze the fatty acid profile in red blood cell membranes of patients with Non-Alcoholic Fatty Liver Disease (NAFLD), in order to identify and validate membrane profiles possibly associated with the degree of hepatic damage. This work presents data obtained at baseline from 101 subjects that participated to a nutritional trial (registration number: NCT02347696) enrolling consecutive subjects with NAFLD. Diagnosis of liver steatosis was performed by using vibration-controlled elastography implemented on FibroScan. Fatty acids, extracted from phospholipids of erythrocyte membranes, were quantified by gas chromatography method. The subjects with severe NAFLD showed a significant decrease of the ratio of stearic acid to oleic acid (saturation index, SI) compared to controls, 1.281 ± 0.31 vs 1.5 ± 0.29, respectively. Low levels of SI in red blood cell membranes, inversely associated with degree of liver damage, suggest that an impairment of circulating cell membrane structure can reflect modifications that take place in the liver. Subjects with severe NAFLDalso showed higher levels of elongase 5 enzymatic activity, evaluated as vaccenic acid to palmitoleic acid ratio. Starting from these evidences, our findings show the importance of lipidomic approach in the diagnosis and the staging of NAFLD.